Au/Go Based Partially Uncladded SMF for Detection of Glucose Concentration - Nurulshahida Syafinie Fauzi; Wan Maisarah Mukhtar; Razman Mohd Halim; Affa Rozana Abdul Rashid; Nur Athirah Mohd Taib (Trans Tech Publications, Ltd., 2026)
Tier 2- Indexed by ERA